Transitions between color categories mapped with a reverse Stroop task - SMITHSON, HANNAH E.; KHAN, SABAH S.; SHARPE, LINDSAY T.; STOCKMAN, ANDREW (Visual neuroscience, 2006)
In the reverse Stroop task, observers are instructed to ignore the ink color in which a color word is printed (the distractor color) and to respond to the meaning of the color word (the target). Reaction times (RTs) are faster with congruent combinations when the ink color matches the word than with incongruent combinations when the ink color does not match the word. We manipulated the distracting ink color from congruent to incongruent and measured the transition from facilitation to interference. In Experiment 1, we confirmed that this transition could be assessed independently from the contextual influence of particular sets of stimuli and responses, implying that the color space in which interference and facilitation occurs is generalizable. In Experiment 2, we obtained reverse Stroop data for transitions between red and yellow, yellow and green, green and blue, and blue and red, and compared them with independent estimates of color appearance obtained by hue scaling for the same chromaticity samples. We find that the magnitude of the reverse Stroop effect can provide a reliable index of the similarity of color appearance between the distracting chromaticity and the color category represented by the target color word. Moreover, it will allow us to quantify the mapping between the chromaticity space defined at the cone photoreceptors and a cognitive color space defined at an advanced level of neural processing.